2022
DOI: 10.3390/jcm11164914
|View full text |Cite
|
Sign up to set email alerts
|

Cystoid Macular Edema after Rhegmatogenous Retinal Detachment Repair with Pars Plana Vitrectomy: Rate, Risk Factors, and Outcomes

Abstract: (1) Background: The aim was to describe the rate and outcomes of cystoid macular edema (CME) after pars plana vitrectomy (PPV) for primary rhegmatogenous retinal detachment (RRD) and to identify risk factors and imaging characteristics. (2) Methods: A retrospective consecutive case study was conducted over a 5-year period among adult patients who underwent PPV for primary RRD repair. The main outcome measure was the rate of CME at 12 months following PPV. (3) Results: Overall, 493 eyes were included. The CME r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 37 publications
3
10
0
Order By: Relevance
“…In the present study, a multivariate analysis showed two independent risk factors associated with the occurrence of CME, in particular the presence of severe PVR and the use of laser retinopexy. Our results are consistent with previous studies that investigated the development of CME after PPV showing that PVR is one of the major risk factors involved [17][18][19]. Additionally, three studies that exclusively included RRD with severe stages of PVR showed higher rates of CME, ranging from 33% to 52% [20][21][22].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In the present study, a multivariate analysis showed two independent risk factors associated with the occurrence of CME, in particular the presence of severe PVR and the use of laser retinopexy. Our results are consistent with previous studies that investigated the development of CME after PPV showing that PVR is one of the major risk factors involved [17][18][19]. Additionally, three studies that exclusively included RRD with severe stages of PVR showed higher rates of CME, ranging from 33% to 52% [20][21][22].…”
Section: Discussionsupporting
confidence: 92%
“…To date, few authors evaluated the prevalence and risk factors of postoperative CME after n number, M male, F female, CME cystoid macular edema RRD repair with PPV [18]. Recently, three studies showed a prevalence between 10% 17% of patients undergoing PPV [17][18][19]. Our results are in agreement with those reported.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In fact, recent studies have highlighted that the incidence of CME after rhegmatogenous retinal detachment repair was higher in patients who underwent PPV, either alone or combined with phacoemulsification than in those treated with SB [ 29 ]. Probably, the use of cryotherapy retinopexy instead of endolaser retinopexy [ 30 ] plays a role in lowering the risk of post-operative CME.…”
Section: Discussionmentioning
confidence: 99%